71.4k views
4 votes
Find the solution of the system by graphing

y=x+1
3x+3y=-9
Part B: The solution to the system, as an ordered pair,

Find the solution of the system by graphing y=x+1 3x+3y=-9 Part B: The solution to-example-1
User Jokarl
by
4.3k points

1 Answer

2 votes

Answer:

x = -2

y = -1

(-2, -1)

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination
  • Solving systems of equations by graphing

Explanation:

Step 1: Define systems

y = x + 1

3x + 3y = -9

Step 2: Solve for x

Substitution

  1. Substitute in y: 3x + 3(x + 1) = -9
  2. Distribute 3: 3x + 3x + 3 = -9
  3. Combine like terms: 6x + 3 = -9
  4. Isolate x term: 6x = -12
  5. Isolate x: x = -2

Step 3: Solve for y

  1. Define original equation: y = x + 1
  2. Substitute in x: y = -2 + 1
  3. Add: y = -1

Step 4: Graph systems

Check the solution set.

Find the solution of the system by graphing y=x+1 3x+3y=-9 Part B: The solution to-example-1
User Illia Bobyr
by
5.2k points